Population and the Japanese economy : - Yoshikawa, Hiroshi (Japan Publishing Industry Foundation for Culture (JPIC), 2020)
This book sweeps away the "population decline pessimism" that has spread throughout Japan and approaches the real issues of the Japanese economy.